Direct operation or delegation? Post-concession port infrastructure governance under risk preference and demand volatility - Minghua Xiong; Weiting Yang; Jiancong Liang; Mingjun Zhan (Frontiers in Marine Science, 2026)
Public-private partnership, or PPP, is now widely adopted for developing port infrastructure worldwide. As these PPP projects near the end of their concession periods, governments are confronted with a key strategic challenge: achieving smooth transition and sustainable operation for these mature infrastructure assets. This paper centers on the core governance decision for post-concession port infrastructure—whether governments should take direct charge of operation or delegate management to private entities—and develops a strategic decision-making framework that fully accounts for private operators’ diverse risk attitudes (ranging from conservative to aggressive) and the inherent volatility of market demand. We first define the First-Best social welfare benchmark corresponding to direct public operation through theoretical analysis, then model the delegated operation mode as a classic principal-agent problem. Our analytical results confirm that the operator’s risk preference is the intrinsic root cause of operational decision distortions (in terms of service price and service level) under delegation, while market environmental uncertainty acts as a synergistic factor that amplifies such deviations, ultimately leading to service degradation and reduced maritime supply chain resilience. The core contribution of this study lies in deriving an optimal risk-contingent regulatory mechanism: we find that the per-unit subsidy must serve as a dynamic incentive and risk-hedging tool, with its parameter settings directly tied to the operator’s risk preference and demand volatility, so as to accurately offset the misalignment of private operational behaviors and ensure the achievement of socially optimal output levels. Most importantly, we establish a specific governance viability threshold: delegated operation is only optimal when the private sector’s operational efficiency advantage is substantial enough to outweigh the social welfare friction costs caused by risk-driven distortions; otherwise, reverting to direct public operation yields superior social and economic outcomes. This research provides maritime regulators with a prescriptive toolkit for managing the critical transition period of port asset governance.